Managing yield and resilience in a harvested tri-trophic food chain model. (21st May 2019) - Kar, Tapan Kumar; Pal, Debprasad; Ghosh, Bapan
Highlights: Balancing yield and resilience in a tri-trophic food chain model. Harvesting the prey at MSY level causes acute resilience loss. Top predator harvesting at MSY level is the most favorable strategy. Only the MSY policy could not be a management benchmark. Simultaneous harvesting with a species oriented fishery is a better choice. Abstract: In this article, we compare the two ecological services known as yield and resilience, for a tri-trophic food chain model consisting of a prey, an intermediate predator and a top predator. For this comparison process, we use both analytical and numerical techniques. It is shown that a variety of patterns are possible based on the intensity of efforts distributed among different trophic levels. Thus we may suggest that fishing down the food chain, as suggested byPauly et al. (1998) is not bound to happen. Our analysis also shows that balancing the harvest between prey, intermediate predator and top predator could give more yield and stabilizing the ecosystem, than the selective harvesting of any one species. This balanced harvesting may not be a win–win situation for yield and resilience, but it could be a most favourable strategy to balance them. This research would help to correlate resilience with yield and determines the desirable selection of two policies, resilience maximizing yield or maximum sustainable yield to safeguard ecological communities.